Sustainable Cellulose Enables Blue Energy Toward Osmotic Energy Conversion - Wang, Yingchao; Shi, Jianping; Zhang, Qianhong; Wu, Hui; Miao, Qingxian; Huang, Liulian; Chen, Lihui; Ni, Yonghao; Li, Jianguo (Nano-Micro Letters, 2026)
The development of osmotic energy technologies offers a sustainable and renewable pathway to address global energy shortages and environmental challenges. Cellulose-based membranes have been increasingly recognized for their remarkable potential in osmotic energy conversion, owing to their intrinsic ion-selective transport properties, structural and chemical tunability. This outstanding performance is primarily attributed to the renewable origin, versatile surface chemistry, and mechanical robustness of cellulose, which collectively facilitate the design of sustainable and durable ion-conducting membranes. This review highlights recent advances in the design and application of cellulose-based membranes for salinity-gradient energy harvesting, with an emphasis on material composition, nanoscale structural engineering, surface functionalization, and optimization of the ion transport approach. Despite these advances, key challenges that hinder further performance enhancement are identified and critically discussed, along with potential strategies for practical large-scale implementation. Furthermore, recent advances in nanoarchitectonic design and chemical functionalization have demonstrated significant improvements in power density, long-term operational stability, and overall membrane performance under diverse salinity and environmental conditions, underscoring the promise of cellulose-based membranes for next-generation blue energy technologies. Highlights: 1 This review highlights the design and application of cellulose-based membranes for salinity-gradient energy harvesting. 2 Material composition, nanoscale structural engineering, surface functionalization, and ion-transport regulation strategies are discussed. 3 Stability, robustness, and scalability are systematically evaluated, and emerging strategies directly relevant to practical applications are summarized.